Production of Poly-L-Lactic Acid from L-Lactic Acid Isolated from Kitchen Waste Fermented Using Enterococcus Gallinarum Eb1 - Ooi, Kim Yng (2006)
Lactic acid (LA) has potential applications in the chemical and biodegradable plastics industries. The L-form LA monomer can be polymerized to polylactate, a degradable polymer with potential to substitute certain environmentally recalcitrant plastics. In the previous work, a local bacterial strain, Enterococcus gallinarum EB1 was found to be a good L-lactic acid producer, with kitchen waste as the substrate. The fermentation of treated kitchen waste contained a mixture of organic acids with mainly lactic acid. The objectives of this study are, i) to produce, recover and purify L-lactic acid from treated kitchen waste by E. gallinarum EB1, and, ii) to produce poly-L-lactic acid (PLLA) from purified L-lactic acid. The fermentation was carried out in 90 L fermenter with a working volume of 60 L. The bacterium converted saccharified kitchen waste into organic acids with mainly lactic acid. The highest lactic acid concentration produced was 59 g/L, with an optical purity of L-lactic acid of 84%. The yield based on total sugar was 0.98 g LA/ g total sugar and the productivity was 0.308 g/L.h. In the recovery process, the concentrated broth was esterified in order to produce butyl lactate. The ester was then subjected to pre distillation and distillation for further purification of butyl lactate. After the separation and purification by distillation, the purity of butyl lactate increased from 40% to 98%. Butanol and lactic acid were produced by hydrolysis of the purified butyl lactate. The purity of lactic acid was 99.6% after hydrolysis. The purified lactic acid was then subjected to dehydration and oligomerization process in order to produce lactide. This lactide contains meso-, D- and L-lactide. Therefore, L-lactide was further purified using toluene in order to achieve 100% purity. Finally, poly-Llactide (PLLA) was produced from L-lactide by ring-opening polymerization. The molecular weight (Mw) of PLLA obtained from this polymerization was 6, 192 g/mol.